Developing a Contextual Learning Model in Islamic Education to Improve Applicable Knowledge and Foster Knowledge-Based Virtues - Muhamad Parhan; Syahidin Syahidin; Momod Abdul Somad; Mulyana Abdulah; Risris Hari Nugraha (Jurnal Pendidikan Islam, 2024)
This study addresses the prevalent reliance on theoretical-abstract learning in Islamic religious education, which often emphasizes theories, symbols, textual materials, and memorized facts. Recognizing the need for a more practical approach, our research aims to develop a contextual learning design specifically focused on prayer in Islamic religious education. The goal is to enhance both knowledge acquisition and the cultivation of charitable virtues. Utilizing a combined quantitative and qualitative research approach, we employed research and development (R&D) methods. Data collection involved participatory observation, documentation studies, and questionnaires. The findings reveal that the contextual learning model significantly improves students' theoretical understanding and practical application of prayer. Results show enhanced academic achievements and the integration of prayer values into students' daily lives. The contextual learning model presents a more realistic, concrete, engaging, and meaningful approach to prayer instruction, fostering active student participation and the application of learned material in real-life scenarios. This study underscores the potential of contextual learning in transforming Islamic religious education, making it more effective and relevant for students.